2015
DOI: 10.1097/cad.0000000000000263
|View full text |Cite
|
Sign up to set email alerts
|

Carvacrol inhibits proliferation and induces apoptosis in human colon cancer cells

Abstract: Colon cancer is one of the most common malignancies worldwide and has a high mortality rate. Carvacrol is a major component of oregano and thyme essential oils and shows antitumor properties. Here, we investigated the effects of carvacrol on the proliferation and apoptosis of two human colon cancer cell lines, HCT116 and LoVo, and studied the molecular mechanisms of its antitumor properties. We found that carvacrol inhibited the proliferation and migration of the two colon cancer cell lines in a concentration-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(88 citation statements)
references
References 30 publications
5
82
0
1
Order By: Relevance
“…Several reports have shown that CV exhibits strong cytotoxic, genotoxic, and proapoptotic activity against cancer cells, in a dosedependent manner, also with effects on cell invasion by reducing the expression of matrix metalloprotease 2 and 9 (Fan et al, 2015). A plethora of cancer cells, indeed, have been tested, including mouse B16 melanoma (He et al, 1997), Hep-2 human larynx carcinoma cells (Stammati et al, 1999), gastric carcinoma cells (Günes-Bayir et al, 2017) leiomyosarcoma cells (Karkabounas et al, 2006), chronic myeloid leukemia cells, K562, A549 non-small-cell lung cancer cells, MDA-MB-231 human metastatic breast cancer cells (Arunasree, 2010;Baranauskaite et al, 2017;He et al, 1997;Koparal & Zeytinoglu, 2003;Lampronti et al, 2006), and human colon cancer cells (Fan et al, 2015). reported in B16 melanoma cells in mouse when treated with CV (He et al, 1997).…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…Several reports have shown that CV exhibits strong cytotoxic, genotoxic, and proapoptotic activity against cancer cells, in a dosedependent manner, also with effects on cell invasion by reducing the expression of matrix metalloprotease 2 and 9 (Fan et al, 2015). A plethora of cancer cells, indeed, have been tested, including mouse B16 melanoma (He et al, 1997), Hep-2 human larynx carcinoma cells (Stammati et al, 1999), gastric carcinoma cells (Günes-Bayir et al, 2017) leiomyosarcoma cells (Karkabounas et al, 2006), chronic myeloid leukemia cells, K562, A549 non-small-cell lung cancer cells, MDA-MB-231 human metastatic breast cancer cells (Arunasree, 2010;Baranauskaite et al, 2017;He et al, 1997;Koparal & Zeytinoglu, 2003;Lampronti et al, 2006), and human colon cancer cells (Fan et al, 2015). reported in B16 melanoma cells in mouse when treated with CV (He et al, 1997).…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…For instance, β-caryophyllene oxide, a sesquiterpene isolated from the essential oils of medicinal plants including oregano, showed an anticancer effect through blocking the STAT3 activation pathway in cancer cells [246]. Moreover, carvacrol induced apoptosis via the mitochondrial apoptotic pathway and the MAPK and PI3K/Akt signaling pathways in colon cancer cells [247]. …”
Section: Other Spicesmentioning
confidence: 99%
“…In human cancer, antiproliferative and cytotoxic properties of carvacrol have been demonstrated in lymphoma (Bhakkiyalakshmi et al, ), colon cancer (Fan et al, ), glioblastoma (Chen et al, ; Liang & Lu, ), hepatoma (Melušová, Jantová, & Horváthová, ), neuroblastoma (Aydın, Türkez, & Keleş, ), oral cancer (Liang et al, ), cervical cancer (Mehdi, Ahmad, Irshad, Manzoor, & Rizvi, ), metastatic breast cancer (Arunasree, ), chronic myeloid leukemia (Horvathova, Turcaniova, & Slamenova, ), leiomyosarcoma (Karkabounas et al, ), nonsmall cell lung cancer (Koparal & Zeytinoglu, ), and melanoma cells (He, Mo, Hadisusilo, Qureshi, & Elson, ), which are mainly attributed to reactive oxygen species‐mediated apoptosis. However, the mechanism of carvacrol‐induced cancer cell cytotoxicity has not been elucidated, neither the possibility of a drug–phytochemical interaction.…”
Section: Introductionmentioning
confidence: 99%